Functional crosstalk between nitrate and ammonium transporters in N acquisition and pH homeostasis - Rivero-Marcos, Mikel (Frontiers in Plant Science, 2025)
In quantitative terms, nitrogen (N) is the most important essential mineral element for plants, acquired mainly in the form of ammonium (NH4+) and nitrate (NO3-). Despite fluctuations in soil NH4+and NO3-availability, plants seek to balance their NH4+-to- NO3-uptake ratio to avoid the metabolic burden associated with the compensation of an intracellular proton excess or deficit. However, while the molecular mechanisms by which plants mediate and modulate the activity of their uptake systems for NO3-and NH4+have been well characterized, it has remained unclear to what extent these transport systems could interact. In this review, the potential contributions of AMTs and NRT1.1 to the overall acquisition of N are highlighted. Both NO3–independent and -dependent signaling of NRT1.1 in modulating NH4+tolerance, as well as the underestimated role of AMTs in nutrient and cellular pH homeostasis, are discussed. The interdependency between AMTs and NRT1.1 is considered highly relevant for optimized N uptake in field conditions, where both N forms typically coexist and act complementarily to maintain balanced pH and nutrient homeostasis for optimal plant growth